A Systemic Contribution and Vulnerability of Non-financial Firms: A Cross Industry Analysis - Zafar Azam; Abdul Raheman; Abdul Rashid (NUML International Journal of Business & Management)
This paper quantifies the systemic importance of non-financial firms by assessing their contribution and vulnerability to systemic shocks. We apply two firm-specific measures, namely Delta CoVaR (ΔCoVaR) and Marginal Expected Shortfall (MES), to evaluate the systemic risk of 205 non-financial firms listed on the Pakistan Stock Exchange over the period from 2005-2021. We apply quantile regression methodology to quantify (ΔCoVaR). We confirm that a significant number of firms contribute to both system-wide shocks and are vulnerable to systemic risk of the whole system. We find that firms with a high-risk score in one area are not always high-risk in another. Measures of systemic risk vary significantly across time, between firms and industries. Energy and transport industries are top contributors to systemic risk however, tobacco and pharmaceuticals are among the top industries that are vulnerable to systemic risk of the whole system. We conclude that non-financial firms are systemically important and this risk should be mitigated. This research offers significant insights for policymakers and other relevant stakeholders both domestically and internationally. It aims to help policymakers examine their macro-prudential policy, which now solely takes into account financial firms, to limit the risk that can spread throughout the entire system.